2021
DOI: 10.1111/mmi.14722
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ entry at the plasma membrane and uptake by acidic stores is regulated by the activity of the V‐H+‐ATPase in Toxoplasma gondii

Abstract: Ca2+ is a universal intracellular signal that regulates many cellular functions. In Toxoplasma gondii, the controlled influx of extracellular and intracellular Ca2+ into the cytosol initiates a signaling cascade that promotes pathogenic processes like tissue destruction and dissemination. In this work, we studied the role of proton transport in cytosolic Ca2+ homeostasis and the initiation of Ca2+ signaling. We used a T. gondii mutant of the V‐H+‐ATPase, a pump previously shown to transport protons to the extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…These differences would impact Ca 2+ storage pools, affecting cytosolic Ca 2+ and signaling. For example, our findings indicate that bradyzoites show reduced responses to ionomycin and thapsigargin, which release Ca 2+ primarily from the ER, and in response to NH 4 Cl, which releases Ca 2+ from acidocalcisomes and likely other acidic stores ( Moreno and Zhong, 1996 ; Stasic et al, 2021 ). Consistent with these dampened responses, bradyzoites showed significantly reduced expression of the Ca 2+ -ATPases TgSERCA ( Nagamune et al, 2007 ) and TgA1 ( Luo et al, 2004 ), which are involved in transporting cytosolic Ca 2+ into the ER and acidocalcisome, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…These differences would impact Ca 2+ storage pools, affecting cytosolic Ca 2+ and signaling. For example, our findings indicate that bradyzoites show reduced responses to ionomycin and thapsigargin, which release Ca 2+ primarily from the ER, and in response to NH 4 Cl, which releases Ca 2+ from acidocalcisomes and likely other acidic stores ( Moreno and Zhong, 1996 ; Stasic et al, 2021 ). Consistent with these dampened responses, bradyzoites showed significantly reduced expression of the Ca 2+ -ATPases TgSERCA ( Nagamune et al, 2007 ) and TgA1 ( Luo et al, 2004 ), which are involved in transporting cytosolic Ca 2+ into the ER and acidocalcisome, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…Based on the above findings, it is likely that bradyzoites possess different mechanisms to control Ca 2+ homeostasis, including differences in expression of calcium channels, calcium pumps and calcium storage pools relative to tachyzoites. For example, our findings indicate that bradyzoites show reduced responses to ionomycin and thapsigargin, which release Ca 2+ from the ER, and in response to NH 4 Cl, which releases Ca 2+ from acidocalcisomes and likely other acidic stores [35,55]. Consistent with these dampened responses, bradyzoites showed significantly reduced expression of the Ca 2+ -ATPases TgSERCA [34] and TgA1 [36], which are involved in transporting cytosolic Ca 2+ into the ER and acidocalcisome, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Two genes with homology to the yeast VTC proteins ScVtc2p (VTC2) and ScVtc4p (VTC4) were identified in T . gondii and we have shown that the VTC4 subunit colocalizes with the V‐H + ‐ATPase to acidocalcisomes and the PLVAC (Stasic et al, 2021). As polyP is negatively charged, it is most likely involved in chelating positively charged ions like Ca 2+ , Zn 2+ , and others.…”
Section: Molecular Components Of the Plvacmentioning
confidence: 92%